2014
DOI: 10.4103/2229-5178.126023
|View full text |Cite
|
Sign up to set email alerts
|

Skin diseases and conditions among students of a medical college in southern India

Abstract: Introduction:Skin diseases are a common problem among young adults. There is paucity of data about it among medical students. This study aimed to find out the pattern of skin disorders and to describe their association with various socio-demographic factors among medical students.Materials and Methods:This cross-sectional study was conducted in June 2011 in a medical college in Mangalore, Karnataka. Two-hundred and seventy eight medical students were chosen from the 4th, 6th and 8th semester through convenient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
2
17
0
2
Order By: Relevance
“…In other countries, such as India, this was much higher, representing 66.5% of all skin diseases among youth, as well as being more prominent in females, which may be due to genetic differences between populations. 17 Therefore, our results support the hypothesis that skin disease prevalence differs according to many factors, such as environmental, socioeconomic, and racial.…”
Section: Figure 2:-order Of Skin Diseases In Terms Of the Number Of Psupporting
confidence: 77%
See 1 more Smart Citation
“…In other countries, such as India, this was much higher, representing 66.5% of all skin diseases among youth, as well as being more prominent in females, which may be due to genetic differences between populations. 17 Therefore, our results support the hypothesis that skin disease prevalence differs according to many factors, such as environmental, socioeconomic, and racial.…”
Section: Figure 2:-order Of Skin Diseases In Terms Of the Number Of Psupporting
confidence: 77%
“…However, females had more hair disorders, which we believe are induced by pregnancy and breastfeeding, or perhaps because they use hair dyes more often than males, that contain chemicals that could lead to hair damage; a recent study conducted in South India supports this hypothesis. 17 When we compare our results with other studies performed outside Saudi Arabia, eczema was much more prevalent in our area, representing about half of all cases, while in other countries such as India, Nigeria, and Egypt, infections were more prominent. This could be due to the superior quality of healthcare services in Saudi Arabia; according to some studies, eczema is more common in developed countries and infections are more prevalent in developing countries.…”
Section: Figure 2:-order Of Skin Diseases In Terms Of the Number Of Psupporting
confidence: 42%
“…Son muy escasos los estudios anteriores que tratan esta temática, se encontró un estudio de Joseph et al [17], los resultados encontrados en la presente investigación sobre la frecuencia de pérdida de cabello coinciden con los encontrados por este estudio publicado en el año 2014, en 274 estudiantes de una escuela médica del sur de la India. Entre otros resultados el 59,3% presentaron pérdida de cabello.…”
Section: Discussionunclassified
“…Es llamativo cómo una entidad que se creía afectaba con mayor frecuencia personas de edad adulta, empieza a comprometer personas cada vez más jóvenes [20], esta última afirmación soportada con los resultados de esta investigación donde, conociendo que el promedio de edad es de 21 años y por medio de un análisis objetivo, basado en la aplicación de las escalas Hamilton-Norwood para hombres y Ludwig para mujeres, se encontró que en total un 55,7% de la población estudiada presenta problemas de pérdida de cabello. Esta proporción alta encontrada en esta investigación coincide con lo encontrado en las investigaciones de Joseph et al [17] y Ben-Saif et al [18] efectuadas coincidencialmente ambas en estudiantes universitarios de la carrera de medicina. En este estudio, la pérdida de cabello varió significativamente con el programa cursado (p=,000) y en el programa de medicina fue de 72%, el programa que presentó menor proporción fue psicología con 27,5%, y el mayor fue contaduría pública con 85%.…”
Section: Discussionunclassified
“…A cross-sectional study carried out in Sweden showed that 1 st year students indicated experiencing the highest degree of pressure from studies. A gender difference regarding stress levels was also seen, where females reported higher levels of stress than males [9]. Another study done among students of a medical college in southern India of 278 students, among hair morbidities commonest was hair loss seen in 165 (59.3%) cases [10].…”
mentioning
confidence: 92%